2011
DOI: 10.1212/wnl.0b013e318236f0cf
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathologic features associated with Alzheimer disease diagnosis

Abstract: Objective: To examine whether the association between clinical Alzheimer disease (AD) diagnosis and neuropathology and the precision by which neuropathology differentiates people with clinical AD from those with normal cognition varies by age. Methods:We conducted a cross-sectional analysis of 2,014 older adults (Ն70 years at death) from the National Alzheimer's Coordinating Center database with clinical diagnosis of normal cognition (made Յ1 year before death, n ϭ 419) or AD (at Ն65 years, n ϭ 1,595) and a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
47
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 28 publications
7
47
4
Order By: Relevance
“…The authors, however, only used one dimension of the method (NRM vs. AD), when in reality the patients had different causes The clinical diagnosis of AD does not correlate very well with neuropathology, not least in the oldest individuals [37]. This is most probably the reason a minor fraction of those diagnosed with AD have EEG features of normal individuals as seen in figure 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors, however, only used one dimension of the method (NRM vs. AD), when in reality the patients had different causes The clinical diagnosis of AD does not correlate very well with neuropathology, not least in the oldest individuals [37]. This is most probably the reason a minor fraction of those diagnosed with AD have EEG features of normal individuals as seen in figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the MCI patients were followed for at least 2 years, the other clinical groups were diagnosed cross-sectionally and therefore mistakes in diagnosis cannot be ruled out. The methods used in the diagnostic work-up are similar to those used in most other memory clinics, it is likely that the proportion of incorrect diagnoses is of a similar magnitude as in other clinics or 5-15% [37].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study of 180 demented patients (mean age 85±3.4 years), autopsy showed AD in 48%, AD with vascular pathology in 19%, VaD in 11%, DLB in 9%, and dementia of unknown etiology in 13% (Jellinger and Attems, 2010), confirming the notion that a high percentage of demented persons aged 80+ do not met the pathological criteria of AD or were classified as "dementia of unknown etiology" (Crystal et al, 2000;Jellinger, 2001). Non-AD pathology significantly improved precise differentiation between oldest-old and younger age groups (Middleton et al, 2011). …”
Section: Dementia In the Oldest-oldmentioning
confidence: 99%
“…Increased densities of neuritic plaques and NFTs are absent in non-demented patients over age 85-90 (Polvikoski et al, 2006;Prohovnik et al, 2006;Haroutunian et al, 2008;Nelson et al, 2009;Middleton et al, 2011;Jellinger and Attems, 2012), and there is considerable overlap in the pathologies found in demented and non-demented patients (Fernando and Ince, 2004). On the other hand, by age 80-85 years, many cognitively unimpaired subjects may have substantial cortical AD pathology (JL Price et al, 2009), while others found significant positive correlation between the extent of dementia and senile plaque density (p=0.011), but not for the NFT density score (p=0.076) .…”
Section: Dementia In the Oldest-oldmentioning
confidence: 99%
“…A 90+ study revealed significantly less severe Aβ, αSyn and TP'D-43 pathologies and hippocampal lesions in non-demented subjects, while Aβ distribution showed no esssential differences; non-demented individuals had limited hippocampal tau and neocortical Aβ pathology [241]. Non-AD pathology significantly improved precise differentiation between oldest-old and younger age groups [263]. …”
mentioning
confidence: 97%